THE ROLE OF ECONOMIC INTELLIGENCE IN THE IDENTIFICATION OF ENTREPRENEURIAL OPPORTUNITIES - Amina BENMAGHNIA (university Of Eloued جامعة الوادي, 2020)
Nowadays, the promoters of ideas are numerous and the startups are multiplying but it is not all the ideas that emerge and it is not all the startups that succeed, the problem lies in identifying entrepreneurial opportunities that allow to implement ideas into projects. This is why it is necessary to study how these opportunities are determined and how economic intelligence contributes to this. This communication presents an empirical study of startups of Algiers
Intervention
Keywords: The entrepreneurial opportunities; ideas; the economic intelligence; the startups of Algiers; The entrepreneur